2020
DOI: 10.1016/j.cmet.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Use of Statins Is Associated with a Reduced Risk of Mortality among Individuals with COVID-19

Abstract: Highlights d Statin treatment among 13,981 patients with COVID-19 was retrospectively studied d Statin use in this cohort was associated with a lower risk of all-cause mortality d Adding an ACE inhibitor or an ARB did not affect statinassociated outcome in the cohort d The benefit of statins among this cohort may be due to immunomodulatory benefits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
495
11
23

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(575 citation statements)
references
References 55 publications
26
495
11
23
Order By: Relevance
“…It is therefore possible that these small regulatory molecules and their interactions with long non-coding RNAs are part of the COVID-19 pathogenesis. If so, they also provide therapeutic targets and opportunities for intervention, possibly in conjunction with other immunomodulatory efforts ( 165 ) and with agents which may upregulate the expression of NEAT1, such as statins ( 33 ). In conclusion, establishing the interlinks between specific ncRNAs and their targets may augment our understanding of the inflammatory course of COVID-19, aid in designing intervention strategies, and lead to potential novel diagnostic and therapeutic means.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that these small regulatory molecules and their interactions with long non-coding RNAs are part of the COVID-19 pathogenesis. If so, they also provide therapeutic targets and opportunities for intervention, possibly in conjunction with other immunomodulatory efforts ( 165 ) and with agents which may upregulate the expression of NEAT1, such as statins ( 33 ). In conclusion, establishing the interlinks between specific ncRNAs and their targets may augment our understanding of the inflammatory course of COVID-19, aid in designing intervention strategies, and lead to potential novel diagnostic and therapeutic means.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of available data from clinical studies support the protective effect of statins against SARS-CoV-2 infection. Indeed, a number of retrospective studies have shown lower inflammatory parameters, decreased incidence of severe clinical manifestations or reduced mortality rates in COVID-19 patients under statin treatment as compared to those not taking statins [ 41 , 42 ]. However, consistent evidence from prospective studies is not currently available.…”
mentioning
confidence: 99%
“…The powerful current state-of-the-art anti-inflammatory corticosteroid therapy (e.g., dexamethasone) needs to be carefully evaluated in patients with diabetes, because of their well-known secondary diabetogenic adverse effects at high doses. Rather, specific and promising anti-inflammatory compounds, such as anti-IL-6, anti-IL-1, and IL-1Ra, which showed robust reduction in markers of inflammation and improvement in glycemia in many clinical trials ( 17 ), or lipid lowering anti-inflammatory statins ( 19 ) should be considered for the symptomatic therapy for COVID-19 patients with diabetes ( Figure 1B ).…”
Section: Discussionmentioning
confidence: 99%